Planejamento energético em indústrias energo-intensivas: uma abordagem técnica, econômica, ambiental e social - Mancini, Fabrizio Nicolai (2022)
The use of energy by the energy-intensive industries, the first sector in consumption, and its correlation with the generation of greenhouse gases and other environmental and social impacts show an opportunity to insert new indicators and methods to select energy solutions in the energy planning of industries. The aim of the thesis is to propose an energy planning method based on an Energy Management System that allows the choice of energy solutions projects evaluating technical, economic, environmental, and social aspects. To achieve this aim, a descriptive and exploratory research of Energy Management Systems (SGE) and Life Cycle Assessment (LCA) was conducted, designing its processes and fundamental elements and selecting techniques and methods in the systematic review. A theoretical model was construct based on the model objects of the SGE, LCA and documents from the energy planning and energy efficiency sector. A planning method was propose contemplating the mapping of aspects to be used, indicators, choice of tools for energy review and selection of projects ending with the method focused on the Brazilian reality. The identification of aspects in the review and LCA document with recommendations for Brazil was inserted contemplating the types of impacts. The choice of indicators pointed to the importance of benchmarking, especially after simulation with the contributions of sustainability and Environmental, Social and Governance (ESG) reports. The choice of tools pointed out useful alternatives. The execution of the step by step of energy planning for the pulp and paper sector, the third industry in Brazil’s energy consumption. For the pulp subsegment, it proves the application of the method, except for project choice (supplied only data), and it was possible to map elements of the sector, using industry documents and sustainability and ESG reports. It concluded that using LCA to select non-traditional indicators for the sector promote the real measurement of impacts, allowing their accounting. As well as the selection of energy solutions projects that may include a LCA if the energy policy and the SGE of the energy-intensive industry make available resources, common in large projects with legal sócio-environmental requirements.